Pengembangan Media Interaktif Berbasis Videoscribe Terhadap Pemahaman Literasi Keuangan untuk Anak TK Aisyiah Bustanul Athfal 37 Banjarmasin - Noor Baiti; Ikhwatun Hasanah (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2023)
In this era of globalization, the development of science and technology is growing rapidly in education. One of them is the development of learning media. This study aims to develop video scribe media which is audio, visual and motion media that is interactive and can attract children's attention in understanding learning. This media is shown to provide an understanding of financial literacy to children from an early age. Where financial literacy education is important for early childhood so that they are accustomed to managing finances well in the future. In Indonesia, financial literacy education is still quite low, both in the family and at school. Financial literacy is part of accounting. Many people think that it is difficult to understand, especially for early childhood. Therefore this research was developed as a solution to provide a deeper understanding for young children of financial literacy through video scribe media. This research uses Research & Development (R&D) research from Sivasailam Thiagarajan called 4-D namely Define, Design, Develop and Dissemination. The research subject was Kindergarten in Anjir Muara District, Barito Kuala Regency. The result of the research is the compilation of video scribe media. This media can be used to make it easier for teachers and children to understand financial literacy. Children are able to manage and manage money, save on the use of goods and energy, and make wise decisions as priorities for fulfilling needs.